¿Es lícito incorporar la modalidad ad corpus en una compraventa de vivienda en planos? Hacia una interpretación razonable del artículo 1577 del Código Civil - Vásquez Rebaza, Walter (2024)
Ad corpus real estate sales are a globalized transactional modality today. Even though they are designed for exchanges of existing real estates, the transactional practice shows that this modality is frequently applied (especially in standardized contracting) to the presale real estate agreements. This extrapolation has resulted in more than a few legal problems where INDECOPI has intervened in ways that are not always uniform.This work will analyze the problem of the scope of application of article 1577 of the Civil Code (which governs the “as is” clause) and its consequences on private and consumer real estate contracts. This is a complex issue that has been doctrinally and jurisprudentially addressed in our country but with a non-particularly ambitious nor convincing focus.